Development and Evaluation of Metronidazole Microspheres using Starch Isolates of Maize Genotypes as Sustained Release Polymer - Lateef Gbenga Bakre; Aishat Bello; Oluwamisimi Olusanya; Oluyemisi Bamiro (Shiraz University of Medical Sciences, 2023)
Genetic engineering of maize plants for improved yield, drought and pest resistance has received considerable attention in agricultural research. This work aims to develop metronidazole microspheres using starches obtained from genetically modified maize cultivars as controlled release polymers. Metronidazole microspheres were prepared by ionotropic gelation method using polymer blend of starches (A and B) isolated from genetically modified maize grains and sodium alginate. The microspheres were characterized using scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). A 32 factorial design was employed using the entrapment efficiency, time taken for 50% (T50) and 90 % (T90) drug release as dependent variables while A, B and polymer-drug ratio were independent variables. SEM reveals that the formulations are polyhedral, hard and discrete with a smooth surface. Metronidazole microspheres formulations containing starch isolates from maize genotypes had significantly higher (p<0.05) entrapment efficiency. Formulations containing a blend of starch and alginate showed a more sustained release than the formulations having only alginate. Values of T90 ranged between 6.12±3.20 to 47.13±7.01 hrs suggesting a sustained release of the drug. Generally, drug release from the microspheres was through erosion and polymer relaxation The effect of type of polymer on the dissolution times was more significant (p<0.05) than those of polymer: drug ratio. This result shows that starches obtained from genetically modified maize grains can be employed as sustained release polymers in the formulation of metronidazole microspheres.